Competitive activity of highly skilled freestyle wrestlers at the present stage - Boyko, V. F.; Malinsky, I. I.; Andriitsev, V.A.; Yaremenko, V. V. (Physical Education of Students, 2014)
Purpose: to compare competitive activity of highly skilled freestyle wrestlers after making adjustments to the wrestling rules. Material: the analysis involved 80 bouts performed by high skilled wrestlers at 2011 World Wrestling Championships (Ankara, Turkey) and 2012 Olympic Games in London (weight categories 84 and 96 kg). Results: the resultant technical actions have been analyzed in the standing position performed by highly skilled freestyle wrestlers in major events of the annual cycle for the last three years. The characteristic changes in a competitive activity of highly skilled freestyle wrestlers in the weight categories 84 and 96 kg have been determined. We identified the techniques which were used most frequently in different periods of bout by elite athletes: spurt moving, throwing by knock, pressing, pushing the mat, etc. Conclusions: the competitions in the training of athletes are not only a means of controlling the level of preparedness, the process for deciding the winner, but also an important means of improving fitness and sports mastership. In the future, specialists can use these features of competitive activity in determining the overall training strategy of freestyle wrestlers to competitions at various levels.